Circulating microRNAs in insulin resistant horses and ponies - Santos, Hugo Felipe da Costa; Hess, Tanja Maria; Brummer, Jason; Graham, Peter; Mcintosh, Brigett; Splan, Rebecca (Brazilian Journal of Veterinary Medicine, 2021)
Insulin resistance is a prevalent disorder among horses and is associated with abnormal adiposity, laminitis, equine metabolic syndrome, and pituitary pars intermedia dysfunction. The processes leading to equine insulin resistance and associated conditions remain subject for study. MicroRNAs (miRNAs) are involved in regulation of many biological processes and diseases. The current study aimed to investigate the circulating miRNA profile of insulin resistant horses and ponies. It was hypothesized that insulin resistant horses would have a different circulating miRNA profile compared to healthy ones. 12 Thoroughbred/ Thoroughbred-cross and 12 Welsh/Dartmoor non-pregnant mares were evaluated for insulin sensitivity using frequent sampling intravenous glucose tolerance test (FSIGTT). Serum samples were collected for miRNA profiling through RT-qPCR analysis. Horses and ponies were divided into insulin sensitive (IS) or insulin resistant (IR) groups and their miRNA profiles compared. Results demonstrated that 13 miRNAs were differently expressed between IR and IS horses, 15 between IR and IS ponies, 17 between horses and ponies, and 10 between IR and IS animals (horses and ponies combined) (p<0.05). Finally, 8 miRNAs were proposed as potential regulators of equine insulin resistance. miRNA profiling is a potential tool to evaluate insulin resistance and associated conditions.